Study the Causality between Agricultural Production and GDP in Syria (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The research aims to investigate the causality between agricultural production and GDP in Syria during the period between 1987 and 2020, to identify the direction of the causality between them. Using the Granger and Toda-Yamamoto Causality tests, and analysis of the dynamic effects and the relative importance of the shocks occurring for each variable.The study concluded that there is a short-term causality and a long-term causality in one-way that goes from agricultural production to GDP in Syria. There is a high ability of the agricultural production to explain the variation in forecast errors in the GDP in the long term, and the analysis of response functions showed that a random shock in agricultural production has a low negative effect on GDP in the short term and a high positive effect in the long term. Historical analysis curves showed that GDP is highly responsive to shocks in agricultural production in the short term.